Molecular‐Level Insights into the Diffusion of a Hydrophobic Drug in a Disordered Block Copolymer Micelle by Molecular Dynamics Simulation. Issue 2 (23rd November 2021) - Razavilar, Negin; Hanna, Gabriel
Abstract: Previously, all‐atom molecular dynamics (MD) simulations of a single hydrophobic drug molecule in pseudo‐micelles (consisting of one polymer chain surrounded by several water molecules) were used to gain insight into drug diffusion in nano‐sized micelles. Although it was shown that hydrogen bonding dominates the drug diffusivity, it was not clear to what extent a pseudo‐micelle model captures the drug diffusion dynamics in a full micelle. Since drug release from a stable drug‐loaded micelle occurs on very long timescales, all‐atom MD simulations of the drug diffusion are prohibitively costly. To reduce the computational cost, herein, an all‐atom MD simulation is performed starting from a disordered structure of a full Cucurbitacin B (CuB)‐loaded poly (ethylene oxide‐b‐caprolactone) block copolymer micelle in water. It is found that both the CuB and water dynamics yield nonlinear sub‐diffusive mean‐squared displacements, which result from molecular crowding in the micelle environment and extensive hydrogen bonding interactions between the water/CuB molecules and polymer chains. Moreover, it is found that the hydrogen bonding and diffusion dynamics in the pseudo‐micelle are not representative of those in the full micelle. The computational approach used herein is expected to yield molecular‐level information that can aid in understanding in‐vitro drug release data from nano‐sized micelles. Abstract : Diffusion of Cucurbitacin B (CuB) drug molecules in a disordered polyethylene oxide‐b‐caprolactone (PEO‐b‐PCL) micelle in water is investigated via all‐atom molecular dynamics. Results show that diffusion of CuB from core to exterior of micelle is mediated by breaking of water‐PEO and formation of water‐PCL/CuB hydrogen bonds. The approach allows one to efficiently gain molecular‐level insights into drug diffusion in micelles.